Numerical analyses for regression rate solid fuel doped with high entropy alloys in hybrid rocket motor - Ismail, Izham Izzat; Asmun, Siti Nurfaiqah; Abdullah, Nur Azam; Azami, Muhammad Hanafi; Nordin, Norhuda Hidayah (2021)
In this paper, a numerical study on the usage of high entropy alloys (HEAs) as additives in solid fuel of hybrid rocket motor is done to investigate the fuel regression rate. Hybrid rocket offers a variety of advantages that include a safer handling method and storage, a more versatile fuel, and a more reliable engine. Despite its advantages, a hybrid rocket engine holds a major drawback which is a low regression rate. Nowadays, metallic ingredients such as metal and light metal are commonly used to improve the regression rate. Herein, Collaborative research is done by adding multi-component alloys, HEAs (Cobalt-Chromium-Iron-Nickel and Aluminium-Cobalt-Chromium-Iron-Nickel) as energetic additives to paraffin wax fuel. High entropy alloys have been proven to be beneficial in their mechanical properties, however, in this paper we will be studying the numerical solutions from the available data to see its behavior and its regression rate as a fuel in the hybrid rocket. Current test results reveal an increase in the regression rate of 84.6 percent for 8 kg/m2s and 74.5 percent for 14 kg/m2s as compared to pure fuel. The performance of the Hybrid rocket motor will improve with a higher regression rate.